Design of a ducted fan for an unmanned aerial vehicle - Tay, Rooney Yong Seah. (2009)
The development of ducted fan propulsion systems in the model and full scale light aircraft has shown steady increase in the recent years due to its advantages under static and low speed thrust. This work is focused on the conceptual design, fabrication and testing of the ducted fan blades in an existing Vertical Take-Off Landing Unmanned Aerial Vehicle (UAV) that employs the ducted fan as the main propulsion system. The ducted fan UAV consists mainly of a fan blade enclosed in an open ended tube. It is similar to a helicopter but have several advantages over it. A systematic design process is followed to achieve a suitable design to support the requirements of the UAV. The fabrication of the fan blade with selection of suitable materials marked the end of the design process. The thrust experiment is performed to compare the performance of the designed fan blades over the existing RC aircraft propellers. The fabricated piece was found to have some limitations during the experiment and possible future tweaks could be implemented.